An Estimation Method of the Solar Irradiance and Electricity Production in the Photovoltaic Systems - SPOIALA Viorica (Journal of Electrical and Electronics Engineering, 2024)
The paper presents an estimation method of the solar irradiance and the electricity production, in different conditions, in the photovoltaic systems. Some simulations were made, for a house electrical installation in the area of the Oradea municipality. The solar irradiance is one of the environmental factors that have major effects to the performance of the photovoltaic panels. Also, the angle of inclination, is one of the system factors that must be considered. Following the simulation with several types of panels from the point of view of the materials from which they are made, it was observed that the values in the case of using crystalline silicon are the most profitable in most cases. The values of the electricity production depend on the month of the year and, also, on the fixing system of the photovoltaic panels. The accuracy, the validity and the efficiency of the study are proven through the experimental results presented in the final part of the manuscript.